Glut9-mediated Urate Uptake Is Responsible for Its Protective Effects on Dopaminergic Neurons in Parkinson’s Disease Models - Bi, Mingxia; Jiao, Qian; Du, Xixun; Jiang, Hong (Frontiers in Molecular Neuroscience, 2018)
Considerable evidence has shown that elevated plasma or cerebrospinal fluid (CSF) urate levels correlated with a reduced risk of Parkinson’s disease (PD). Based on its anti-oxidative properties, urate might serve as one of promising neuroprotective candidates for PD. However, how urate is transported through cell membranes to exert its effects inside the cells in PD is largely unknown. To elucidate this, we showed that increased intracellular urate exerted its neuroprotective effects against 1-methyl-4-phenylpyridinium (MPP+)-induced neurotoxicity in MES23.5 cells and elevated urate could antagonize 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigral dopaminergic neuronal death in urate oxidase (UOx) knockout mice. Its transporter, glucose transporter type 9 (Glut9), was observed up-regulated, which was caused by the activation of p53. These protective effects could be abolished by Glut9 blocker and p53 inhibitor. These results suggested that Glut9 was a functional urate transporter, whose up-regulation by activation of p53 resulted in the increased intracellular urate levels in PD models. Our findings suggest that Glut9 could be modified to modulate urate levels in dopaminergic neurons and urate-elevating strategies without increasing systemic levels to avoid side effects might serve as a potential therapeutic target for PD.